HUBUNGAN POLA MAKAN DAN POLA ISTIRAHAT DENGAN PRODUKSI ASI PADA IBU MENYUSUI DI PMB BD REHLIASNA SEBAYANG TAHUN 2024 - Hanum, Parida; Rusiana, Rusiana; Sitepu, Erlita; Turnip, Lasmaida (STIKes William Booth Surabaya, 2025)
Background: Breast milk production can increase or decrease depending on the stimulation of the breast glands. Several factors affect breast milk production such as frequency of breastfeeding, birth weight, gestational age at delivery, stress and acute illness, alcohol consumption, cigarette consumption, contraceptive pills, maternal diet, husband and family support, breast care, type of delivery, and joint care. The purpose of this study was to determine the relationship between diet and rest patterns with breast milk production in breastfeeding mothers. Methode: The type of research used was quantitative using an analytic observational design research design with a cross sectional approach. The population in this study were all breastfeeding mothers totaling 75 people. The technique of taking subjects using total sampling of 75 people. The data collection method used was to use a questionnaire that was prepared to measure variables. diet, rest patterns and milk production. Data analysis was univariate and bivariate analysis with chi square test. Result: The results explained that there was a relationship between diet (p=0.000) and rest patterns (p=0.013) with breast milk production in breastfeeding mothers. Discussion: The conclusion of this study is that there is a relationship between diet (p=0.000) and rest patterns (p=0.013) with breast milk production in breastfeeding mothers